Isolation and characterisation of major histocompatibility complex gene class I and II in Malayan tapir (Tapirus indicus Desmarest) - Ismail, Nurul Adilah (2019)
Malayan tapir is one of the five tapir species in the world and is listed as endangered in the IUCN Red List due to multiple threats such as habitat loss and human disturbance that lead to its high population decline. Low population number in this species increase the risk of inbreeding that could result in reduction in genome-wide genetic variation and particularly risky if it affects the gene responsible for immune response i.e. MHC gene. Class I and II MHC genes are responsible for encoding MHC molecules in the cells that recognise pathogenic peptides and present them to T-Cells on the cell surface for adaptive immune response. However, at present there is no study related to MHC gene in Malayan tapir yet. This study characterise the MHC peptide-binding region (PBR) of the MHC class I and II gene in Malayan tapir by isolating the DNA, amplify the targeted region by PCR, cloning and sequencing; investigate if there is evidence of balancing selection by calculating the rate of non-synonymous (dN) and synonymous (dS) substitutions using MEGA and PAML and study its relationship with homologous genes of other species based on phylogenetic tree construction alongside two DRA, two DQA, three DRB and three DQB of class II alleles were evidence of selection with dN /dS > 1. A total of 24 codons within exon 2 DRB gene were found to be under selection with ten of the codons under positive selection sites (PSS) are part of the codons forming the Antigen Binding Site (ABS). Class I αI and α2 sequences formed two separate groups on phylogenetic tree when compared to other species indicating possibility of two different loci. Within class II genes, all genes show species specific monophyletic group formation except for DRB genes with intersperse relationship in their phylogenetic trees which may indicate occurrence of trans-species polymorphism of allelic lineage. To maintain and improve the variation within the MHC gene, it is recommended to genotype tapir at the MHC gene to avoid mating with similar MHC allele and variation.